City Love and Neighbourhood Resilience in the Urban Fabric: A Microcosmic Urbanometric Analysis of Rotterdam - Kourtit, Karima; Nijkamp, Peter; Turk, Umut; Wahlstrom, Mia (Elsevier, 2022)
Ups and downs in city life are dependent on the citizens' appreciation for their urban 'home', in particular the neighbourhood liveability. Taking modern research on urban wellbeing and happiness as a point of departure, this study presents and tests a new methodology for assessing the residents' affection for their local neighbourhood. This approach is inspired by the 'city love' concept and seeks to examine and decompose city love through an analytical distinction into the 'body and soul' of the city. Using a rich multi-period and geographically detailed database on neighbourhoods in the city of Rotterdam, including distinct social capital indicators for analysing social resilience in urban areas, a microcosmic decomposition of objective and subjective socio-economic information is carried out. On the basis of geo-science visualisation methods and advanced spatial-econometric techniques for handling neighbourhood autocorrelation effects ('urbanometrics'), a series of explanatory regression analyses is executed in order to identify and explain the determinants of city love at neighbourhood level in Rotterdam. We find that bonding and bridging social capital are prominent in shaping neighbourhood love and social resilience.
Turk, Umut/0000-0002-8440-7048; Kourtit, Karima/0000-0002-7171-994X; Nijkamp, Peter/0000-0002-4068-8132;
Keywords: City Love; Neighbourhood Resilience; Happiness Research; Body and Soul; Microcosmic; Urban Informatics; Decomposition; Urbanometrics